2012
DOI: 10.1186/1472-6793-12-15
|View full text |Cite
|
Sign up to set email alerts
|

VEGF induces sensory and motor peripheral plasticity, alters bladder function, and promotes visceral sensitivity

Abstract: BackgroundThis work tests the hypothesis that bladder instillation with vascular endothelial growth factor (VEGF) modulates sensory and motor nerve plasticity, and, consequently, bladder function and visceral sensitivity.In addition to C57BL/6J, ChAT-cre mice were used for visualization of bladder cholinergic nerves. The direct effect of VEGF on the density of sensory nerves expressing the transient receptor potential vanilloid subfamily 1 (TRPV1) and cholinergic nerves (ChAT) was studied one week after one or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 91 publications
2
41
2
Order By: Relevance
“…Other roles for VEGF-VEGF receptor system in the lower urinary tract may involve inflammation-induced lymphangiogenesis and angiogenesis (Saban et al, 2010; Saban, 2015). The present studies demonstrating increased VEGF transcript expression in the urothelium and detrusor of WT and NGF-OE mice with CYP-induced cystitis are consistent with previous studies demonstrating contributions from the VEGF-VEGF receptor system in the structure and function of the lower urinary tract (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other roles for VEGF-VEGF receptor system in the lower urinary tract may involve inflammation-induced lymphangiogenesis and angiogenesis (Saban et al, 2010; Saban, 2015). The present studies demonstrating increased VEGF transcript expression in the urothelium and detrusor of WT and NGF-OE mice with CYP-induced cystitis are consistent with previous studies demonstrating contributions from the VEGF-VEGF receptor system in the structure and function of the lower urinary tract (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). …”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that animal models of urinary bladder inflammation and BPS/IC regulate the VEGF-VEGF receptor system in the urothelium (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). Increased expression of VEGF and receptors has been reported in bladder biopsies from women with BPS/IC and expression of VEGF correlates with pain described by patients (Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant increased expression of VEGF in bladder biopsied tissues has been reported in IC/BPS patients compared with controls, which was associated with the degree of pain . The basic research findings have shown that intravesical instillation of VEGF modulated sensory and motor nerve plasticity, and, consequently, bladder function and visceral sensitivity in rats . In addition, systemic anti‐VEGF neutralizing antibody pretreatment significantly reduced the pelvic nociceptive response to cyclophosphamide‐induced cystitis compared with controls in rats .…”
Section: Discussionmentioning
confidence: 88%
“…NGF induces VEGF expression in sensory neurons in the dorsal root ganglion (DRG), suggesting further cross‐talk between sensory neurons and blood vessels. Exogenous, intravesicular VEGF administration increased peripheral nerve density and pain . The influence of VEGF on pain may occur indirectly from VEGF stimulation of angiogenesis and sensory neuron ingrowth or inflammation.…”
Section: Introductionmentioning
confidence: 99%